2020
DOI: 10.1002/ccr3.2987
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐induced copper deficiency, sideroblastic anemia, and neutropenia: A perplexing facet of zinc excess

Abstract: Hypocupremia due to zinc products can cause sideroblastic anemia and neutropenia and mimics other serious hematological disorders. Early consideration of the copper deficiency and a thorough clinical history can prevent unnecessary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Heavy metal toxicity, specifically from lead poisoning or zinc overdose is associated with SA. Excess exposure to zinc can cause SA by competing with iron incorporation into protoporphyrin and preventing intestinal absorption of copper through induction of an intestinal metal-binding protein metallothionein [13].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metal toxicity, specifically from lead poisoning or zinc overdose is associated with SA. Excess exposure to zinc can cause SA by competing with iron incorporation into protoporphyrin and preventing intestinal absorption of copper through induction of an intestinal metal-binding protein metallothionein [13].…”
Section: Discussionmentioning
confidence: 99%
“…In several small studies, zinc gluconate showed promising results in mild-to-moderate HS [ 64 , 65 , 66 ]. As zinc competes with copper in gastrointestinal resorption, long-term use of high doses of zinc may cause hypocupremia and anemia; thus, routine monitoring of copper levels and hemoglobin is recommended [ 67 ]. Gastrointestinal discomfort is a frequent reported side effect.…”
Section: Treatmentmentioning
confidence: 99%
“…Ceruloplasmin is a ferroxidase that helps to convert ferrous to ferric iron, allowing it to bind transferrin and be transported throughout the body. The enzyme cytochrome oxidase, which is copper-dependent, is required for the reduction of ferric iron and incorporating it into the Heme molecule [ 82 , 83 , 84 ]. Copper deficiency can develop hematological abnormalities, and it might mimic myelodysplastic syndromes [ 85 , 86 , 87 , 88 , 89 ].…”
Section: Non-clonal or Metabolic Acquired Sideroblastic Anemiasmentioning
confidence: 99%